Strategy In Teaching English Vocabulary - Alviani Alviani (CV. Rayyan Dwi Bharata, 2023)
The objectives of the research were to find out how inquiry based strategy is effective to improve the students’ achievement. The design of the research was classroom action research. It was done in two cycles, while every cycle consisted of four steps (planning, acting, observing, and reflecting). The first cycle conducted in two meetings include pre-test. The second cycle was conducted in two meetings and each cycle the students were taken the test as the post-test. The subjects of this research were 8 students of Grade two SMKS Analis Palopo. Based on the result of this research showed that there was an improvement on the students’ vocabulary, it can be seen from the mean score of pre-test were 57,5, the mean score of post-test I was 69, and the mean score of post-test II was 83. In addition, there was 1 students (12,5%) who passed Minimum Mastery Criterion (Kriteria Ketuntasan Minimal/KKM) in the pre-test. Meanwhile, in the cycle I, there were 3 students (37,5%) who passed Minimum Mastery Criterion (KKM), and in the post-test II there were 7 students (87,5%) who passed Minimum Mastery Criterion (KKM), so the criteria of success was achieved. Then, from the result of questionnaire it showed that there was improvement of positive responses in the teaching-learning process of vocabulary through Inquiry strategy. The mean of pre-questionnaire was 41,84%. Then, the mean of post-questionnaire was 77,6%. It improved 35,76%. Furthermore, the results of observation and interview showed that the students were motivated in teaching-learning process during the implementation of Inquiry strategy.